Effect of Training for Care Providers on Practice of Essential Newborn Care in Hospitals in Sri Lanka - Senarath, Upul; Fernando, D.N.; Rodrigo, Ishani (My University, 2007)
Objective : To evaluate the effectiveness of a training program for care providers in improving practice of essential newborn care in obstetric units. Design : Before-and-after study with an intervention and a control group. Setting : Five hospitals in the Puttalam district in Sri Lanka. Participants : Eight hundred and ninety-two mother-newborn pairs (446 before and 446 three months after). Intervention : A 4-day training program on essential newborn care for doctors, nurses, and midwives of the obstetric units in two hospitals. Main Outcome Measures : By direct observation, practices of essential newborn care at delivery in the labor room on a subsample. By interviewing mothers, immediate skin-to-skin contact and early initiation of breastfeeding. From health records, “ undesirable health events ” of the newborns. Results : Practices of cleanliness, thermal protection, and neonatal assessment improved signifi - cantly in the intervention group. The intervention was effective in improving skin-to-skin contact by 1.5 times and early initiation of breastfeeding by 3.4 times. Undesirable health events declined from 32 to 21 per 223 newborns in the intervention group and from 20 to 17 per 223 newborns in the control group. Conclusion : A comprehensive 4-day training program can be followed by a signifi cant improvement in essential newborn care practices in obstetric units.